STUDI KASUS PARTISIPASI MASYARAKAT PADA DINAMIKA SOSIAL BUDAYA SASI LAUT DESA TAAR KOTA TUAL - Novalin Chrisnatalia Leleury; Esti Setiawati Setiawati; Sukadari (Program Magister Pendidikan IPS UPY, 2025)
This study aims to analyze community participation in the socio-cultural dynamics of the sasi laut practice in Taar Village, Tual City, Maluku Province as a form of local wisdom that plays a crucial role in coastal resource management. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation. The collected data were analyzed using an interactive technique consisting of data reduction, data presentation, and conclusion drawing, in order to obtain a comprehensive understanding of community involvement in sustaining the sasi laut practice. The findings of this research are expected to demonstrate that community participation is reflected in active involvement in customary deliberations, collective monitoring of designated marine areas, and compliance with prevailing customary norms and regulations. Furthermore, sasi laut functions not only ecologically in maintaining marine ecosystem sustainability but also embeds socio-cultural values that strengthen solidarity, collective identity, and communal cohesion of the indigenous community. These findings are expected to reaffirm that sasi laut constitutes a form of local wisdom–based resource management that is relevant to supporting natural resource sustainability while simultaneously reinforcing the socio-cultural order of the local community. Keywords: community participation, sasi laut, socio-cultural dynamics, local wisdom